2023
DOI: 10.1038/s42949-022-00081-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and scenario hypothesis of food waste in China based on material flow analysis

Abstract: Field research limits the possibility of clarifying the current food waste situation in China. Material flow analysis was used to assess the magnitude and characteristics of waste in five stages from 2010–2019 by seven selected types. Wheat was wasted the most at 38%, while milk was wasted the least at 4%. During post-harvest handling and storage, processing and packaging, and consumption, wheat was wasted the most (56%, 36%, and 48%), while during production and marketing, tomatoes were wasted the most (28% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Additionally, the Partnership for African Fisheries Governance Working Group stated that it is projected that the fishing industry would lose USD 2 billion annually (de Graaf & Garibaldi, 2015). It was reported that the majority of freshwater fish is lost during production due to the use of substandard fishing gear, non‐targeted fishing and a lack of policy enforcement in fishery management (Jiang et al., 2023). According to the report, the majority of fish processing methods are inhumane, which lowers the quality of fish products.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the Partnership for African Fisheries Governance Working Group stated that it is projected that the fishing industry would lose USD 2 billion annually (de Graaf & Garibaldi, 2015). It was reported that the majority of freshwater fish is lost during production due to the use of substandard fishing gear, non‐targeted fishing and a lack of policy enforcement in fishery management (Jiang et al., 2023). According to the report, the majority of fish processing methods are inhumane, which lowers the quality of fish products.…”
Section: Resultsmentioning
confidence: 99%
“…MFA is a quantitative method used to study and quantify the flow of materials, substances and energy within a system defined in space and time and the results that flow (Kaufman, 2012;Voukkali and Zorpas, 2022). MFA does not require the involvement of participants and is able to accommodate large sample sizes, offering greater precision in calculations (Jiang et al, 2023). Since MFA depicts the linear correlation of material flow, it implies that the total input must be equivalent to the total output generated.…”
Section: Mfamentioning
confidence: 99%